PENINGKATAN SKILL DAN DIGITAL MARKETING INDUSTRI MAKANAN PADA USAHA MIKRO â€œCAHAYAâ€ PASURUAN - Sri Utami Ady; Alvy Mulyaningtyas; Litafira Syahadiyanti; Fany Meyranda Putri; Mar'atus Sholikhah; Duvan Hermansyah Yudi Astono (Jurnal Abdi Insani, 2023)
The home industry is a household craft business with 1-4 workers. The home industry that was a partner in this PKM was the "CAHAYA" Micro Enterprise. The partner problems were: 1. Business management, which was still conventional, 2: finance, 3. Marketing was still minimal. The target to be achieved was that Partners could improve knowledge, skills, and quality of human resources, make financial reports, and use promotional tools through social media. to increase the knowledge and skills of partners to help improve the income of the "CAHAYA" Micro Business to increase its contribution to the family economy through training in business governance, finance, and digital marketing. PKM activities carried out include training, practice, and assistance in culinary business management, training in preparing financial reports according to accounting principles, training and assistance in using social media Instagram, WA business, and TikTok as well as FGD (Focus Group Discussion) with culinary entrepreneurs. The results of this service were increased knowledge and skills of partners in business governance, financial management, and the use of social media for promotions, as well as increased sales. Conclusion: This PKM activity has been able to improve Partners' knowledge and skills to increase their contribution to the family economy, becoming more independent, creative, and efficient MSMEs.